1H-NMR and HPLC–MS/MS-based global/targeted metabolomic evaluation of Hypericum perforatum L. intervention for menopause. (August 2015) - Liu, Yan-Ru; Xiao, Bing-Kun; Yang, Jian-Yun; Guo, Chun-Hua; Shen, Shu-Jie; Tang, Zhi-Shu; Dong, Jun-Xing; Huang, Rong-Qing
Highlights: A metabolomic-based mechanism of Hypericum perforatum L. for menopause was elucidated. Targeted and global metabolomic approaches for metabolites analysis were established by 1 H-NMR and HPLC–MS/MS. Hypericum perforatum L. intake recovered 23 of 53 menopause abnormal metabolites. Four major metabolic pathways including the 23 quantified metabolites might contribute to the HPL intervention. Abstract: Hypericum perforatum L., which includes a wide range of bioactive substances and is sold as a functional food formulation, has been used as an alternative to estrogen replacement treatment to relieve menopausal syndromes. However, methods to track HPL mechanisms and link them to metabolism disorder regulation during menopause periods have been lacking. To investigate HPL function in endocrine-related metabolic recognition, we applied both global and targeted metabolomic methods on ovariectomised rat serum and urine metabolites for treatment-specific metabolic profiling and to explore biomarkers and deduce their mechanisms via 1 H-NMR and HPLC–MS/MS techniques. Results from the comparison of metabolite levels of rats that underwent an ovariectomy (OVX) before and after the administration of different doses of HPL showed that HPL can reverse the disordered changes induced in multiple biomarkers by menopausal syndromes. Through screening, identification, and quantification of the differential regulatory metabolites, 23 metabolites involved in 4 major metabolic pathways, including the arginine, taurine, pyruvate and tryptophan metabolic pathways, were highlighted as important for explaining the mechanisms of HPL. These pathways may be applicable for explanations of other menopausal syndrome symptoms, such as depression and hot flashes, and the effects of other herbs rich in flavonoids with menopause remission potential.